A Perfect narrative of the apprehension, tryal, and confession of the five several persons that were confederates in stealing the mace and the two privy purses from the Lord High-Chancellor of England : as it was attested at the sessions held at Justice-Hall in the Old-Bayly, the seventh and eigth of March, anno. 1676/7. (British trials, 1660-1900 ;, 1677)
The pricipal ring-leader in the robbery was Thomas Sadler, executed at Tyburn the 16th of March, 1677.